Kinetics and mechanism of Oxidation of Cycloheptanol in Acid Solution of N-Bromosuccinicmide - Singh, A.K.; Kumar, Satyendra (Asian Journal of Chemistry, 2010)
The kinetics and mechanism of iridium(III) chloride catalysed oxidationof cycloheptanol by acidic solution of N-bromosuccinimide (NBS) havebeen extensively studied at constant temp. (35°C). Kinetic findings indicatefirst order reaction kinetics in oxidant, substrate, Ir(III) and reductant ineach case. Negative effect of chloride ion has been observed on reactionrate while ionic strength of the medium and successive addition ofsuccinimide on reaction rate do not bring any significant change in thereaction velocity. The oxidation reaction path involving NBS, i.e., ΔEa andΔS*, ΔM'* have also been evaluated and found to be 16.72 kcal/mole, -5.83e.u. and 17.88 Kcal/mole respectively and a suitable mechanism consistentwith the observed kinetic finding has been suggested.